Projetos específicos de expansão urbana: perspectivas e desafios à sua implementação na Região Metropolitana de Belo Horizonte - Débora de Luces Sarlo (2015)
The Federal Law No. 12.608/12, enacted in April 10, 2012, deals the enforceability of developing specific design for new municipal urban sprawl areas when changing the urban perimeter. Such normative aspects suggest a concern with the new urban expansion areas, limiting occupancy trends at most favorable areas, taking into consideration the needs of environmental protection, diversification of uses and forecast areas for social housing, avoiding so that the city grow wildly and segregated. This dissertation aims to identify changes in the urban area under this new instrument, its agents, and assess whether the specific projects required will be able to provide better control and territorial sprawl to the urban area, or will be summarized to a step bureaucratic sprawl process. To Achieve the objectives listed above, was reviewed research literature in order to create a theoretical basis about the expansion process and evaluated the process of expansion of the Belo Horizonte metropolitan area, in addition to understanding the role of the state before the metropolis expansion processes. A comparative study of the method for preparing the Specific Project Urban Expansion in three cities that have implemented the instrument was done, including the methodology adopted by the Development Agency of the Metropolitan Region of Belo Horizonte. A review of the sprawl process of the metropolitan area of Belo Horizonte City will be held as well as the evaluation of the institution of property consortiums or land readjustments to subsidize the establishment of these specific projects, and comparative study of the method for preparing of Specific Projects of Urban Sprawl developed by the Agency for Development of the Metropolitan Area of Belo Horizonte, in comparison with the applicable legal procedures for amending the urban area before the advent of the amendment of the Statute of Cities.